Pendampingan Gerakan Pendidikan Lingkungan di 12 Lembaga Pendidikan Dasar (SD & MI) di Area Pendukung Kawasan Konservasi Kebun Raya Purwodadi Kabupaten Pasuruan - Zainul Ahwan; Mochamad Hasyim (LPPM Universitas Yudharta Pasuruan, 2020)
The Environmental Education Movement Assistance Program in 12 Elementary Education Institutions (SD & MI) in the Support Area of ​​the Purwodadi Botanical Garden Conservation of Pasuruan Regency at Capang Village, Kertosari Village and Tejowangi Village Pasuruan Regency has been held for 5 months starting in January - May 2018 Capang Village, Kertosari Village and Tejowangi Village Pasuruan Regency has been held for 5 months starting in January - May 2018. This program has produced a pilot community of adiwiyata education in 3 villages namely the villages of Kertosari, Capang and Tejowangi. Through this program, it has been able to improve the knowledge and skills of teachers and students in 12 basic educational institutions program partners in conducting education to instill environmental care characters in students, in addition, the program partners also have knowledge and skills in environmental management in the school area through school waste banks and planting and utilization of TOGA plants in each school.